Republic of Korea : Financial Sector Assessment Program-Detailed Assessment of Compliance on the Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2014)
SUMMARY, KEY FINDINGS, AND RECOMMENDATIONS The Republic of Korea has a moderate level of compliance with the Basel Core Principles for Effective Banking Supervision (BCP). Building upon the 2003 FSAP recommendations, the authorities have taken resolute steps to strengthen the regulation and supervision of the banking sector. However, the assessment identified gaps that need to be addressed and although the Republic of Korea counts with a strong-albeit overly complex-regulatory framework and with thorough supervisory practices, a number of areas require attention so that the Republic of Korea can meet the highest standards of supervisory effectiveness. Those areas include: broader powers to apply minimum capital requirements to individual banks; full implementation of Pillar 2 and ICAAP; and a more comprehensive approach to conglomerates. The application of Basel II to Financial Holding Companies (FHCs) would complement the transition to group supervision which began through the introduction of the FHC Act. Despite the deficiencies identified in the assessment, the current supervisory structure has been reasonably effective and the overall vulnerability of the Korean banking system has diminished since the 2008 crisis with stronger capitalization across the sector. Supervision of the banks is structured around sound off-site supervision techniques and onsite inspections. Strengths lie in sophisticated offsite monitoring capabilities and an extensive onsite capability. The FSC-FSS collects and analyzes a broad suite of information including detailed financial and management information. The supervisory approach relies heavily on off-site monitoring and notifications of exceptions, which are supplemented by biannual full-scope on-site examinations. The existence of multiple points of responsibility, where subject matter experts are responsible for different areas of surveillance poses challenges of coordination and to derive an overall understanding risk to an institution. The Republic of Korea is one of the first countries to be assessed under the revised Basel Core Principles (BCP) issued by the Basel Committee in September 2012. Like other countries being assessed under the new methodology, the Republic of Korea has agreed to be assessed and rated not only on the essential criteria but also on the additional criteria. It is important to note that since last assessment, conducted in 2003, the bar of the standards has been raised twice by the BCBS (the BCP methodology was revised in 2006 and again in 2012). This assessment, consequently, is not comparable with the previous assessment and, as prescribed by its methodology, should not be compared or across countries. Within the revised BCP methodology, more is expected of supervision and regulation, and much of what was considered 'desirable' is now considered essential, with the lessons of crisis and evolution of financial markets and international standards. The assessment also brings a new relevance to observed implementation and practices.